Dynamic changes in tumor profiling reveal intra- and inter-tumoral heterogeneity focused on an uncharacterized HER2 mutation: a case report of a young breast cancer patient - Schaffrin-Nabe, Dörthe; Josten-Nabe, Anke; Tannapfel, Andrea; Uhl, Waldemar; Garmer, Marietta; Kurzrock, Razelle; Crook, Timothy; Limaye, Sewanti; Schuster, Stefan; Patil, Darshana; Schaffrin, Merle; Mokbel, Kefah; et al. (Frontiers in Oncology, 2024)
Despite recent achievements in breast cancer treatments, we still observe challenging cases where indicated guideline options display limited efficacy. However, the advent of extensive tumor profiling (ETP) as comprising genetic alterations of tissue and ctDNA, immunohistochemistry, circulating tumor cells, gene expression and pharmacogenomics allows to search for solutions aside from guideline options. Here we describe a case taking advantage of multiple comprehensive tumor profilings considering targets, co-alterations and resistance factors. A 46-year-old female was diagnosed with invasive breast cancer of luminal A subtype. After early failure of guideline based chemo-, radiotherapy and surgery followed by endocrine treatment, multiple therapy resistant metastases developed. Treatment strategy was now focused on various individual cancer characteristics after performing extensive tumor profiling (Exacta) whenever progression occured. For the first time after `matching` the patient, we reached long lasting and good partial responses targeting unexpected alterations like the uncharacterized ERBB2 mutation V697L . Furthermore, three alterations, characterized by loss of function, important for double-strand DNA break repair like BRCA1 V627S fs*4 as a germline mutation and somatic alterations of BRCA1 Y101* and ARID1A Q633 Ter were selectively administered. Precision oncology based on ETP is a milestone in personalized treatment as cancer itself is a complex disease with need for complex solutions.